PENDAMPINGAN BELAJAR MENGAJI DAN PENDIDIKAN SEKOLAH BAGI ANAK ANAK SAAT PANDEMI COVID-19 DI DESA KESENENG, MOJOTENGAH, WONOSOBO - Rochmat Arifin (Fakultas Ilmu Tarbiyah dan Keguruan, Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2021)
The Corona COVID 19 virus is currently sweeping the world, Corona virus is a large family of viruses that cause disease in humans and animals. In humans, it usually causes respiratory tract infections, from the common cold to serious diseases such as Middle East Respiratory Syndrome (MERS) and Severe Acute Respiratory Syndrome (SARS). In fact, the spread is also very fast. The Covid-19 pandemic affects all activities of human life starting from sports activities, offices, even to transcendental relationships for all religions in the world, including in the field of education. Educational activities that are closely related to interactions that involve many people; educators with students in a learning environment directly face to face. Due to the covid-19 pandemic, interaction has been immediately stopped (social distancing) and replaced with distance learning activities (online) by utilizing internet media. Because distance learning (online) has been going on for quite a long time, it makes children or students like elementary school children learning difficulties and they feel bored. Even the parents of the parents have started to have difficulties because it is not uncommon for the parents to not understand their children's learning materials. In addition, of course, many parents are busy working. With the learning assistance, it is hoped that it will be able to help children in learning and lighten the burden on parents.